Effects of motor stimulation of the tibial nerve on corticospinal excitability of abductor hallucis and pelvic floor muscles - Eginyan, Gevorg; Zhou, Xueqing; Williams, Alison M. M.; Lam, Tania (Frontiers in Rehabilitation Sciences, 2023)
Peripheral nerve stimulation can modulate the excitability of corticospinal pathways of muscles in the upper and lower limbs. Further, the pattern of peripheral nerve stimulation (continuous vs. intermittent) may be an important factor determining the modulation of this corticospinal excitability. The pelvic floor muscles (PFM) are crucial for maintaining urinary continence in humans, and share spinal segmental innervation with the tibial nerve. We explored the idea of whether the neuromodulatory effects of tibial nerve stimulation (TibNS) could induce effects on somatic pathways to the PFM. We evaluated the effects of two patterns of stimulation (intermittent vs. continuous) on corticospinal excitability of the PFM compared to its effect on the abductor hallucis (AH) muscle (which is directly innervated by the tibial nerve). We hypothesized that intermittent TibNS would increase, while continuous stimulation would decrease, the excitability of both AH and PFM. Twenty able-bodied adults (20-33 years of age) enrolled in this study. TibNS was delivered either intermittently (1 ms pulses delivered at 30Hz with an on:off duty cycle of 600:400 ms, for 60 min), or continuously (1 ms pulses delivered at 30Hz for 36 min) just above the motor threshold of the AH. We randomized the order of the stimulation pattern and tested them on separate days. We used surface electromyography (EMG) to record motor-evoked responses (MEP) in the PFM and AH following transcranial magnetic stimulation (TMS). We generated stimulus-response (SR) curves to quantify the changes in peak-to-peak MEP amplitude relative to TMS intensity to assess changes in corticospinal excitability pre- and post-stimulation. We found that TibNS increased corticospinal excitability only to AH, with no effects in PFM. There was no difference in responses to continuous vs. intermittent stimulation. Our results indicate a lack of effect of TibNS on descending somatic pathways to the PFM, but further investigation is required to explore other stimulation parameters and whether neuromodulatory effects may be spinal in origin.